It's Not Just About Speed: Single-Cell Tracking Reveals Changes in MSC Motility Associated with Replicative Senescence - Lukacheva, Anastasiya V.; Bogachev, Mikhail I.; Musorina, Anastasiya S.; Kriger, Darya V.; Poljanskaya, Galina G.; Bobkov, Danila E. (Stem cell reviews and reports, 2025)
Mesenchymal stem cells, cultured in 2D, are motile fibroblast-like cells with a well-developed actin cytoskeleton. In this study, we analyzed changes in cell motility during long-term cultivation accompanied by replicative senescence (RS) for DF2 and MSCWJ-1 cell lines derived from various sources and donors of different age under both normal and inflammatory conditions, the latter obtained by treatment with lysophosphatidic acid (LPA). Our results indicate that RS is associated with non-stationary alterations in the average migration speed: while the median speed derived from single-cell tracking is unaffected by the senescence stage, the average speed in young cells is enhanced due to the contribution of a subpopulation of fast-moving cells. The sensitivity of cell motility metrics to the impact of LPA varied depending on their origin, with the most pronounced effects observed during the initial passages. Using multivariate statistical analysis, we have shown explicitly that the common motility metrics (average and maximum speed, distance, sinuosity of trajectories, etc.) are associated with the passage, thus clearly reflecting senescence effect. Altogether, our results indicate that cell motility exhibits complex alterations with RS, with multiple metrics besides the average speed being affected and associated with their RS stage. Graphical Abstract